A Case of Recurrent Mesocolon Myxoid Liposarcoma and Review of the Literature. (7th November 2013) - Eltweri, Amar M.; Gravante, Gianpiero; Read-Jones, Sarah Louise; Rai, Sonpreet; Bowrey, David J.; Haynes, Ian Gordon
Abstract : Background . Liposarcoma is the second most common soft tissue sarcoma affecting predominantly the retroperitoneal space and extremities. Mesenteric liposarcoma is uncommon and occurs in the small bowel mesentery. In this paper we report the case of a recurrent mesocolon myxoid liposarcoma manifesting 6 years from the initial right hemicolectomy for the primary tumour. Case Report . A 41-year-old female presented with a 4-day history of signs and symptoms indicative of small bowel obstruction, subsequently confirmed on plain abdominal X-ray. In 2006 she underwent a right hemicolectomy for a myxoid liposarcoma of the mesentery. The patient was initially managed conservatively; however she showed no signs of improvement and was taken to theatre for an exploratory laparotomy and division of adhesional bands. During this procedure an incidental finding of a dark purple, smooth pelvic mass was identified with similar macroscopic appearance to that of splenic tissue. Histological examination revealed a recurrent mesocolon myxoid liposarcoma. Conclusion . Mesocolon myxoid liposarcoma is a rare soft tissue neoplastic pathology and carries a high risk of recurrence. Therefore, a symptomatic patient with a previous history of primary liposarcoma excision should be treated with a high index of suspicion and a longer period of followup should be considered.